RESEARCH ON TEST METHOD OF FUSELAGE PANEL SUBJECTED TO INTERNAL PRESSURE LOAD - ZANG WeiFeng; DONG DengKe; ZHANG HaiYing (Jixie qiangdu)
The test method of fuselage panel subjected to internal pressure load is an important technique for aircraft structure strength research.The constraint simulation technique for the curved and straight boundaries of fuselage panel was studied based on boundary requirements.A test method using "D"jig to simulate the straight boundary conditions and airproof end-plate to simulate the curved boundary conditions of fuselage panels were proposed.A test panel and a set of fixtures were designed and manufactured,and validation tests were conducted.Measured stresses in test are reasonably distributed and are consistent with theoretic result.The proposed test method is proven to be proper and valid,and it provides reference for configuration-selection tests of fuselage panel subjected to internal pressure load.